THE INFLUENCE OF THE TAXATION SYSTEM, GENDER, LOVE OF MONEY, AND UNDERSTANDING OF THE THREE TABOOS ON STUDENT PERCEPTIONS REGARDING TAX EVASION - Prastyatini, Sri Lestari Yuli; Chaerunisak, Uum Helmina; Sinta, Restika Putri Ayunda (International Conference on Humanity Education and Society (ICHES), 2024)
Tax evasion cases are rife in Indonesia, involving taxpayers and tax officers. Tax evasion has a negative connotation and is classified as a criminal offense because it is carried out intentionally in violation of the law and can harm the nation. As taxpayers, students need knowledge related to tax evasion. So this research was carried out comprehensively regarding students assumptions about the influence of taxation system variables, gender, love of money, and understanding of Tamansiswa's three taboos. This research was carried out using quantitative methods which include data processing and data presentation, carrying out calculations to describe the data and carrying out hypothesis testing. The results of the research show that the taxation system and understanding the Tamansiswa three taboos have a negative effect on students' perceptions of tax evasion, while gender and love of money have a positive effect on students' perceptions of tax evasion. This research provides views and insights regarding student perceptions regarding the taxation system in Indonesia which is influenced by several factors. However, there are 39.9% other variables that were not examined by the author as limitations.